Typification and nomenclatural clarifications of names related to the genus Nototriche (Malvaceae) - Cialdella, Ana M.; O’leary, Nataly (Phytotaxa, 2019)
Twenty-six lectotypes (including one as a second step designation, and another as an holotype to be corrected to lectotype, according to Art. 9.10 of the ICN, Turland et al. 2018) and two neotypes are here proposed for twenty-eightnames related to the genusNototriche, as part of the ongoing study on the genus for the South American flora. Notes about typifications are provided.